The Application of Communicative Language Teaching to Improve Students’ Ability in Speaking - Nurhayati Sitorus (Universitas Cokroaminoto Palopo, 2019)
The purpose of this study is to investigate students’ ability in speaking before and after using Communicative Language Teaching in learning English. The method in this research was experimental quantitative method by using quasi experimental design with one group pretest-posttest model. The design only see students’ achievement in speaking before and after using Communicative language Teaching. The object of the research was English Department students. They were randomly selected. The technique of collecting the data was done through observation and the data were gotten from the students when they did oral communication. The instrument in this research was oral test. The data were analyzed by using Lilliefors test, testing homogeneity F, and testing hypothesis by using T-test. The result of this study shown that the use of Communicative Language Teaching could improve students’ ability in speaking. It was proved from the students’ average was higher after using Communicative Language Teaching. The data in this research had normal distribution. Based on data analysis by using T-test was gotten that tcount = 6,59 at the significant level = 5% and dk (n-1) = (30-1) =29 was gotten ttable = 1,699. So, tcount > ttable. It proved that Ho was rejected, and Ha was accepted. It’s meant that there was a significant difference between students’ ability before and after implementing Communicative Language Teaching.